Complejo ecoturístico como elemento articulador al sur del departamento del Huila (2022)
In the following work of degree of architectural approach, an identification of the most representative tourist places of the department of Huila is disclosed, with the objective of solving a tourist problem in the south of the department, due to the waste of the tourist impact that exists between the municipality of Suaza and Florencia (Caquetá), a connection with great tourism potential which will be a catalyst for future social and tourism projects in the region, thus